Designing Task Complexity in Promoting Language Performance - Nik Aloesnita, Nik Mohd Alwi; Umi Kalsom, Masrom (Centre for Engineering Education (CEE) UTM, 2016)
The concern over low English language proficiency and performance among Malaysian learners has been explored extensively. This situation calls for the innovation in English language teaching which is more practical and applies student-centered approaches. This paper therefore intends to examine the effects of task complexity on language performance using task-based instruction. Based on the empirical evidence of this study, teachers could gain more understanding on how tasks could be manipulated in learning English as a Second Language (ESL) via computer-mediated communication (CMC) to enhance language performance.